2020
DOI: 10.3390/antiox9080749
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Profile of the Pain-Relieving Antioxidant Compound Thioctic Acid in Its Racemic and Enantiomeric Forms

Abstract: Thioctic acid is a multipotent antioxidant compound existing as dextrorotatory (+), eutomer and naturally occurring and levorotatory (−). It has been proven to help fight many pathologies and is sold as racemate. In agreement with studies claiming a greater biopotency of the eutomer compared to the levorotatory compound, we recently preclinically and clinically showed that (+) thioctic acid is a pain-reliever as effective as double-dosed racemate. We investigated acute and subchronical toxicity of (+/−) thioct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The supplementation of lipoic acid as natural antioxidant has already been demonstrated to be safe in clinical trials [83], and to have multiple beneficial effects [57]. In particular, (+)-ALA showed the most pronounced activity, with extremely few acute and subchronic toxicities, compared to all the forms of ALA [84].…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of lipoic acid as natural antioxidant has already been demonstrated to be safe in clinical trials [83], and to have multiple beneficial effects [57]. In particular, (+)-ALA showed the most pronounced activity, with extremely few acute and subchronic toxicities, compared to all the forms of ALA [84].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the clinical study confirmed the efficacy of the antioxidant thioctic acid in the treatment of the peripheral neuropathy without differences in male and female ( Memeo and Loiero, 2008 ; Ranieri et al, 2009 ; Agathos et al, 2018 ; Mrakic-Sposta et al, 2018 ; Salehi et al, 2019 ; Passiatore et al, 2020 ) being also characterized by good safety profile which makes it suitable for prolonged treatment even in the chronic phase of this disease ( Ametov et al, 2003 ; Ziegler et al, 2006 ). Anyway, it should be carefully prescribed and monitored since the possibility of side effects as recently emerged in a preclinical toxicologic study ( Lucarini et al, 2020 ). The results of clinical study show a greater effectiveness of (+)-thioctic acid compared to (+/−)-thioctic acid in terms of major impact on pain symptoms, rapidity of therapeutic effects onset and, more generally, better quality of life, as confirmed by the response rate to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence that (+)-ALA was more active than (±)- or (-)-enantiomers in reducing oxidative stress and may be more effective against nanomaterial-induced injuries ( 55 , 56 ). However, no included studies reported the isomer information of used ALA. Sixth, although our subgroup analyses suggested the ALA dose seemed not to influence the anti-oxidant, anti-inflammatory and chelation effects, it was known that ALA was also not completely free from side effects, particularly (–) enantiomer-treated animals that were found to display more marked organ toxicity signs ( 57 ). Thus, low-dose ALA should be recommended theoretically.…”
Section: Discussionmentioning
confidence: 89%
“…Clinically, ALA is commonly used for the treatment of diseases related to the nervous system ( 53 , 54 ). Although the neuroprotective mechanisms may be complex, anti-oxidant and anti-inflammatory effects of ALA play main roles ( 53 57 ), indicating ALA supplementation may antagonize nanomaterial-induced neurotoxicity. In line with the expectation, we found the AchE, an enzyme that mediates the neuromuscular impulse transmission and promotes regeneration of neurites, in rats exposed to nanomaterials was significantly increased by ALA treatment, which was accompanied by improved pathological changes of cerebrum neuron ( 19 , 35 ).…”
Section: Discussionmentioning
confidence: 99%